KOMUNIKASI ANTAR BUDAYA ETNIS JAWA DENGAN ETNIS TIONGHOA DALAM PROSESI GREBEG SUDIRO DI KAMPUNG SUDIROPRAJAN SURAKARTA - Sri Lestari, Maya Sekarwangi, Nurnawati Hindra (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2018)
ABSTRACTGrebeg Sudiro was created as new culture to unite assimilation of Javanese and Chinese ethnics existing in Surakarta. This cultural rite was held by Sudiroprajan multiethnic people to unite Javanese and Chinese Ethnics in Jebres Sub District, Surakarta City in 2007. Sudiroprajan village is called as Chinese (Pecinan) village in Surakarta. Different Javanese and Chinese traditions were combined well and merrily as two large ethnics composing Sudiroprajan community in Grebeg Sudiro helped with participation by outsiders. In this Grebeg Sudiro there were Buk Teko and Kue Keranjang particularly as the symbols that should exist every year.The method employed in this research was descriptive qualitative one with scientific research approach aiming to conceive a phenomenon in social context naturally by emphasizing on an in-depth communication interaction process between author and phenomenon studied. To complete the data, the author interviewed the informants to answer her questions. Limited book and other supporting literature, and many people not knowing or recognizing Grebeg Sudiro cultural rite were the reasons of why this research was important to conduct, thereby can be the basis of more in-depth research in the future. This research was very closely related to Communication Science, particularly Cross-culture Communication in order to realize the peaceful life in this world. Grebeg Sudiro was a connector to connect the messages from communicator (Sudiroprajan people) to communicant (Surakarta people). The message of Grebeg Sudiro was communicated by means of communication symbol such as gunungan, jodang karya seni, art carnival, annual theme. The communication symbol was coupled in the frame of community unity in Surakarta City. Keywords: Cross-Culture Communication, Grebeg Sudiro Procession